Conservation Strip Tillage Leads to Persistent Alterations in the Rhizosphere Microbiota of Brassica napus Crops - Rathore, Ridhdhi; Dowling, David N.; Forristal, Patrick D.; Spink, John; Cotter, Paul D.; Germaine, Kieran J. (Frontiers in Soil Science, 2021)
Microbes play vital roles in many soil ecosystem functions and services, which are crucial for agricultural productivity. Among different agricultural management practices, soil tillage methods can result in changes in a soil's physical, chemical and biological properties, including the soil microbiome. In addition, crop type and the plant developmental stage are important drivers of rhizosphere bacterial microbiota structure and composition. Here, we have used high-throughput, 16S amplicon sequencing to explore the rhizosphere bacterial structure and composition of Brassica napus (winter oilseed rape) in two contrasting tillage practices; conventional-plough based tillage and conservation strip tillage, over three different plant growth stages (vegetative, flowering and harvesting stage). This was the first year that conservation strip tillage was used in this field, as in previous years plough based tillage practices has been used. Our findings show that tillage and growth stages were important determinants of microbial community structure and composition, but the effect of tillage became stronger at plant maturity. The combined effect of conservation strip tillage and harvesting stage had a impact on the rhizosphere microbiota selection. The rhizosphere bacterial community of winter oilseed rape under conservation strip tillage was different to that under conventional tillage. Our data suggests that different tillage regimes created distinct ecological niches that selected different microbiota with potential consequences for the ecosystem services provided to the plants and the soil environment.